Respuesta :
[tex]q(x) = {x}^{2} + 3x + 4 [/tex]
_________________________________
Step(1)
To find q(a) we just need to put a instead of x in q(x) function.
Let's do it...
[tex]q(a) = {a}^{2} + 3a + 4 [/tex]
Multiply sides by -2 :
[tex] - 2q(a) = - 2( {a}^{2} + 3a + 4) [/tex]
[tex] - 2q(a) = - 2 {a}^{2} - 6a - 8 [/tex]
_________________________________
Step (2)
To find q(a+1) we just need to put a+1 instead of x in q(x) function.
Let's do it...
[tex]q(a + 1) = ({a + 1})^{2} + 3(a + 1) + 4 \\ [/tex]
[tex]q(a + 1) = {a}^{2} + 2a + 1 + 3a + 3 + 4 \\ [/tex]
[tex]q(a + 1) = {a}^{2} + 5a + 8 [/tex]
_________________________________
Step (3)
[tex]q(a + 1) - 2q(a) = [/tex]
[tex] {a}^{2} + 5a + 8 - 2 {a}^{2} - 6a - 8 = \\ [/tex]
[tex] - {a}^{2} - a = - a(a + 1)[/tex]
And we're done.
Thanks for watching buddy good luck.
♥️♥️♥️♥️♥️
The expression for q(a+1) - 2q(a) is -a² - a
Given the expression q(x) = x²+3x+4
First, we need to get the function q(a+1)
q(a+1) = (a+1)²+3(a+1)+4
Expand
q(a+1) = a² + 2a + 1 + 3a + 3 + 4
q(a+1) = a² + 5a + 8
For the function q(a)
q(a) = a²+3a+4
2q(a) = 2(a²+3a+4)
2q(a)= 2a² + 6a + 8
Taking the difference:
q(a+1) - 2q(a) = a² + 5a + 8 - ( 2a² + 6a + 8)
q(a+1) - 2q(a) = a² + 5a + 8 - 2a² - 6a - 8
q(a+1) - 2q(a) = -a² - a
Hence the expression for q(a+1) - 2q(a) is -a² - a
Learn more here: https://brainly.com/question/17581815